2016
DOI: 10.5812/atr.36952
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Chitosan Films Impregnated With Ciprofloxacin for the Prophylaxis of Osteomyelitis in Open Fractures: An Experimental Study in Rats

Abstract: BackgroundThe systemic antimicrobial prophylaxis is the standard treatment in the prevention of osteomyelitis after open fractures, with topical application of antimicrobials as an alternative due to their high concentrations at the site of the fracture, low systemic concentrations and fewer side effects.ObjectivesThis study aimed to evaluate the effectiveness of prophylaxis of osteomyelitis through experimental model of open fractures with the use of chitosan films, whether or not impregnated with ciprofloxac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…These findings corroborate the study by Greenberg et al that described rates of 60% of remaining infection after ciprofloxacin systemic treatment for Staphylococcus aureus osteomyelitis. Similar findings were also encountered in animal models studies by Paiva Costa et al 26 , and Penn-Barwell et al 27 that encountered no infection control after systemic ciprofloxacin as an isolated treatment for osseous Staphylococcus aureus infection in rats.…”
Section: ■ Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…These findings corroborate the study by Greenberg et al that described rates of 60% of remaining infection after ciprofloxacin systemic treatment for Staphylococcus aureus osteomyelitis. Similar findings were also encountered in animal models studies by Paiva Costa et al 26 , and Penn-Barwell et al 27 that encountered no infection control after systemic ciprofloxacin as an isolated treatment for osseous Staphylococcus aureus infection in rats.…”
Section: ■ Discussionsupporting
confidence: 78%
“…The scintigraphy study demonstrated that treatment using 25% and 50% of ciprofloxacin incorporated in the fracture fixation device was effective in preventing bone infection compared to the control group (p<0.05). However, the use of 10% ciprofloxacin was not effective in preventing bone infection, according to the previous study 26 .…”
Section: ■ Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In recent studies, antibiotics, phages, and lysostaphin released from films/coatings made of phosphatidylcholine, 137,138 hydroxypropylmethlycellulose (HPMC), 35 poly(D,L-lactide) (PDLLA), 139 and a hyaluronic acid/poly-lactic acid hydrogel (DAC) 111 have been explored, among others. 97,[140][141][142][143][144][145][146] Interestingly, silver as a coating material may be used as both an antimicrobial and a delivery vehicle, or combined with other materials such as zeolites (made of aluminum and silicon), which are beneficial in this pairing because of their crystal-like porous structure. 97 In one study, zeolite alone decreased bacterial counts by approximately 3000 units.…”
Section: Coatings/filmsmentioning
confidence: 99%